Analgesic effect of ADX71441, a positive allosteric modulator (PAM) of GABAB receptor in a rat model of bladder pain. (November 2017) - Kannampalli, Pradeep; Poli, Sonia-Maria; Boléa, Christelle; Sengupta, Jyoti N.
Abstract: Therapeutic use of GABAB receptor agonists for conditions like chronic abdominal pain, overactive bladder (OAB) and gastroesophageal reflux disease (GERD) is severely affected by poor blood-brain barrier permeability and potential side effects. ADX71441 is a novel positive allosteric modulator (PAM) of the GABAB receptor that has shown encouraging results in pre-clinical models of anxiety, pain, OAB and alcohol addiction. The present study investigates the analgesic effect of ADX71441 to noxious stimulation of the urinary bladder and colon in rats. In female Sprague-Dawley rats, systemic (i.p), but not intrathecal (i.t), administration of ADX71441 produced a dose-dependent decrease in viscero-motor response (VMR) to graded urinary bladder distension (UBD) and colorectal distension (CRD). Additionally, intra-cerebroventricular (i.c.v.) administration of ADX71441 significantly decreased the VMRs to noxious UBD. In electrophysiology experiments, the drug did not attenuate the responses of UBD-sensitive pelvic nerve afferent (PNA) fibers to UBD. In contrast, ADX71441 significantly decreased the responses of UBD-responsive lumbosacral (LS) spinal neurons in spinal intact rats. However, ADX71441 did not attenuate these LS neurons in cervical (C1-C2) spinal transected rats. During cystometrogram (CMG) recordings, ADX71441 (i.p.) significantly decreased the VMR to slow infusion without affecting the number of voiding contraction. These results indicate that ADX71441 modulate bladder nociception via its effect at the supra-spinal sites without affecting the normal bladder motility and micturition reflex in naïve adult rats. Highlights: IC/PBS significantly affects the quality of life of the patient. ADX71441 is a novel positive allosteric modulator of GABAB receptor. Analgesic effect of ADX71441 was investigated in a rodent bladder pain model using behavioral and electrophysiological techniques. ADX71441 exhibits supraspinally mediated analgesic effect against bladder pain. ADX71441 can be a potential therapeutic option for treating IC/PBS in humans.